A new method for optimal sensor placement considering multiple factors and its application to deepwater riser monitoring systems. (15th January 2022) - Zhang, Yulong; Chai, Shuhong; An, Chen; Lim, Frank; Duan, Menglan
Abstract: Various optimal sensor placement (OSP) methods have been developed and widely used in structural health monitoring (SHM). Among them, the effective independence-energy (EI-energy) methods integrating modal observability and system energy, have been attracting growing interest nowadays. However, the EI-energy techniques normally focus on a single energy factor, lacking consideration of the combined effects of multiple energy factors, especially for the large-scale structure with severe vibration and large deformation. To overcome this limitation, a novel multi-factor OSP strategy, namely effective independence-acceleration amplitude-total displacement (EI-AA-TD), is proposed in this study. This new method combines two typical energy indexes, kinetic energy and strain energy, into the classic EI method. The contribution matrixes associated with these two energy indexes are emphatically discussed. Then, the resulting contribution matrixes from energy perspective, and the EI coefficient vector from modal observability perspective are integrated together to formulate a multi-factor optimization framework for sensor placement. Furthermore, a comprehensive scoring evaluation technique is proposed to assess the quality of sensor layout. Finally, the proposed OSP method and evaluation approach are validated through a study case of deepwater riser monitoring systems. The proposed EI-AA-TD method gets an excellent score of 47 (total 50) with the comprehensive scoring evaluation technique. The related results illustrate the effectiveness and superiorities of the proposed methods. Highlights: A novel multi-factor optimal sensor placement (OSP) strategy is proposed. The kinetic energy and strain energy are considered simultaneously as the energy indexes in OSP for the first time. A new comprehensive scoring evaluation technique is presented to assess the quality of sensor layout. The results from a case study of deepwater riser monitoring systems validate the effectiveness of the proposed methods.